Relationship between undrained shear strength and moisture content for red berea sand tailings - Du Plessis, Albertus (My University, 2001)
The project report deals with the relationship between the undrained shear strength and the moisture content of Red Berea sand tailings. The tailings were obtained from the Red Berea sand dunes near Richards Bay, Kwa-Zulu Natal, South Africa. The geology of the area consists of Miocene deposits of red clayey sand, classified as Berea Formation. A method for determining stability of a tailings dam for Red Berea sand tailings, was investigated. The general method of using the degree of saturation of the tailings to specify the rate of rise, is not applicable to this type of tailings. It was found that a relationship exists between the undrained shear strength of the tailings, and the moisture content. The moisture content can easily be measured and the undrained shear strength can then be calculated. The calculated undrained shear strength can be used in a total stress analysis to determine a factor of safety against failure. This project report consists of a discussion of the literature, which was used as the basis for the assumptions made, as well as a description of the tests performed to prove the above-mentioned relationship. Test results are given, interpreted and used in an illustrative example of a stability analysis.
A project report submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Engineering.
Keywords: Tailings embankments; Shear strength of soils; Strains and stresses; Strength of materials